The Disabled 1 Phosphotyrosine-Binding Domain Binds to the Internalization Signals of Transmembrane Glycoproteins and to Phospholipids - Howell, Brian W. (American Society for Microbiology, 1999)
Disabled gene products are important for nervous system development in drosophila and mammals. In mice, the Dab1 protein is thought to function downstream of the extracellular protein Reln during neuronal positioning. The structures of Dab proteins suggest that they mediate protein-protein or protein-membrane docking functions. Here we show that the amino-terminal phosphotyrosine-binding (PTB) domain of Dab1 binds to the transmembrane glycoproteins of the amyloid precursor protein (APP) and low-density lipoprotein receptor families and the cytoplasmic signaling protein Ship. Dab1 associates with the APP cytoplasmic domain in transfected cells and is coexpressed with APP in hippocampal neurons. Screening of a set of altered peptide sequences showed that the sequence GYXNPXY present in APP family members is an optimal binding sequence, with approximately 0.5 μM affinity. Unlike other PTB domains, the Dab1 PTB does not bind to tyrosine-phosphorylated peptide ligands. The PTB domain also binds specifically to phospholipid bilayers containing phosphatidylinositol 4P (PtdIns4P) or PtdIns4,5P(2) in a manner that does not interfere with protein binding. We propose that the PTB domain permits Dab1 to bind specifically to transmembrane proteins containing an NPXY internalization signal.